2013
DOI: 10.1111/ijsw.12010
|View full text |Cite
|
Sign up to set email alerts
|

Effects of US citizenship on wages of Asian immigrant women

Abstract: The article presents a cross‐sectional study on the effects of US citizenship on wages of Asian immigrant women. The findings show that US citizenship positively moderated the relationship between sample characteristics and wages. Higher education (university and graduate school) significantly boosts the wage level of Asian immigrant women who have US citizenship. However, such positive influence does not exist for Asian immigrant women without US citizenship. This finding suggests that Asian immigrant women w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
2
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 70 publications
(78 reference statements)
1
2
0
Order By: Relevance
“…In addition, it is possible that immigrants who naturalize will invest heavily in human capital specific to the host country that will in turn lead to earnings growth. Similar results are found in other European and North American studies (DeVoretz and Pivnenko 2005;Fougère and Safi 2009;Zhou and Lee 2013;Ivļevs and King 2012;Steinhardt 2012). In contrast, Bratsberg and Raaum (2011) find no positive impact-and even a negative impact-of citizenship on the labour market outcomes of immigrants in Norway.…”
supporting
confidence: 91%
“…In addition, it is possible that immigrants who naturalize will invest heavily in human capital specific to the host country that will in turn lead to earnings growth. Similar results are found in other European and North American studies (DeVoretz and Pivnenko 2005;Fougère and Safi 2009;Zhou and Lee 2013;Ivļevs and King 2012;Steinhardt 2012). In contrast, Bratsberg and Raaum (2011) find no positive impact-and even a negative impact-of citizenship on the labour market outcomes of immigrants in Norway.…”
supporting
confidence: 91%
“…Conversely, when they used less family support, the association between perceived racial discrimination and psychological distress was significantly positive for those with low self-esteem, but not for those with high self-esteem. Moreover, two studies examined a glass ceiling effect (i.e., unequal treatment for the foreign born) on Asian immigrants in the U.S. Zhou and Lee (2013) found that higher education significantly boosted the wage level of Asian immigrant women with U.S. citizenship but not of Asian immigrant women without U.S. citizenship.…”
Section: Resultsmentioning
confidence: 99%
“…Although little work exists that makes explicit motherhood penalty comparisons between Asian and nonAsian women, research has found that high-skilled Asian women are less likely to reduce their work hours than similarly skilled white women (Greenman 2011). Zhou and Lee (2013) found no motherhood penalty among Asian women.…”
Section: Gender Revolution and Second-generation Womenmentioning
confidence: 99%